Game study on safety supervision of imported aquatic products in China - Tong, Xia; Gu, Yutong; Yang, Ruirui; Gao, Shenrong (Frontiers in Environmental Science, 2023)
With the expanding scale of aquatic product imports, safety issues have arisen. Among them, the lack of supervision by government agencies, illegal importation by unscrupulous enterprises and the lack of regulatory bodies such as consumers are major reasons for the occurrence of unsafe imported aquatic products. Therefore, this paper adopts a two-by-two static game model between government agencies and importers, importers and consumers, and a three-way sequential dynamic game model between government agencies, importers and consumers to analyze the causes of quality and safety problems of imported aquatic products in China. The results show that when the safety problems of imported fishery products occur, consumers choose to report importers when the compensation they receive due to reporting increases or when the cost of reporting is reduced by not reporting; government agencies choose to strictly regulate importers when the cost of regulation is reduced by loose regulation and reputation loss increases, or when the revenue from fines obtained by strict regulation increases. It is further verified through empirical evidence that both government agency regulation and consumer monitoring have positive effects on importers' self-regulation. Finally, countermeasures to ensure the quality and safety of imported aquatic products in China are proposed.